Penerapan Mesin Pengiling Kedelai Sistem Rotari untuk Meningkatkan Produktivitas usaha Tahu Desa Kalidoh Langensari Barat Ungaran Barat - Abdul Syukur Alfauzi; Yusuf D H; Sahid Sahid; Dita Anies Munawwaroh (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The home industry partner for the tofu business is located in Kalidoh Langensari Barat Village, Ungaran Barat District, Semarang Regency. The partner's obstacle is the failure to meet the increasing market demand. This obstacle is caused because the production process is still carried out manually or traditionally so that tofu production is limited to human power. The right solution offered through this community service is the application of process technology in the form of a soybean grinding machine with a rotary system to increase tofu productivity. The purpose of this community service is to make an electric soybean grinding machine, apply a rotary grinding machine to the tofu production process, and conduct evaluation and assistance to maintain the sustainability of the program. The initial stage carried out in this service consists of planning and making the machine. Planning is based on market needs and partner conditions related to the provision of electrical energy. The design results are made through machine work in the Mechanical Department workshop. The next stage is the application of the machine including assembly and installation of the machine at the partner's location, as well as operational training and machine maintenance. The final stage of the service is evaluation and assistance. Evaluation is carried out by directly assessing the partner's operational practices on the machine that has been assisted. The assistance provided includes supervision, work control, and direction when the partner produces tofu using the production machine. It is expected that the rotary soybean grinding machine can increase the production of partner tofu.